2022
DOI: 10.3390/cancers14143397
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Risk Factors and Etiology of the Canine Oral Mucosal Melanoma: Results of an Epidemiological Questionnaire, Oral Microbiome Analysis and Investigation of Papillomavirus Infection

Abstract: Oral mucosal melanoma (OMM) is the most common oral cancer in dogs and is very aggressive in this species; its risk factors and etiology are yet to be determined. This study aimed to unravel the risk factors for the development of OMM in dogs and to investigate the possible presence of papillomaviruses as an etiological factor. A case-control study was conducted in 15 dogs with OMM and 15 paired controls whose owners answered an epidemiological questionnaire. Oral swabs from the same dogs were subjected to 16S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 37 publications
(62 reference statements)
1
6
3
Order By: Relevance
“…Oral anaerobic bacteria such as Porphyromonas spp., Fusobacterium spp., Bacteriodes spp., Capnocytophaga spp., Prevotella spp., Tannerella spp., Treponema spp., and Actinomyces spp. reported in the previous study [ 29 , 31 , 48 , 70 , 77 , 79 , 80 ] were not found in our study. Some bacterial isolates have been detected from the environment, as the channel of a dog's mouth is exposed to the outdoor environment.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…Oral anaerobic bacteria such as Porphyromonas spp., Fusobacterium spp., Bacteriodes spp., Capnocytophaga spp., Prevotella spp., Tannerella spp., Treponema spp., and Actinomyces spp. reported in the previous study [ 29 , 31 , 48 , 70 , 77 , 79 , 80 ] were not found in our study. Some bacterial isolates have been detected from the environment, as the channel of a dog's mouth is exposed to the outdoor environment.…”
Section: Discussioncontrasting
confidence: 90%
“…They found that Tannerella forsythia and Porphyromonas gingivalis from the subgingival plaque samples were significantly increased in canine oral melanoma dogs compared to the control dogs. These bacterial species are related to the periodontal diseases and human esophageal cancer [ 48 ]. So far, there are few studies that compare the oral bacteria of healthy dogs and dogs with oral cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, tumor-associated microbiomes have been identified in several cancers including one study in cutaneous melanomas [123]. There is only one study in COM; it identified bacteria ( Tannerella forsythia and Porphyromonas gingivalis ) that in humans are key for the development of periodontal disease and esophageal cancer [214].…”
Section: The Influence Of the Gut Microbiome In Melanoma Progression ...mentioning
confidence: 99%
“…While there is evidence on the association between microbiota and neoplastic diseases in dogs [33][34][35][36][37], data on oral bacteria contribution to tumorigenesis in animals is limited. In a study that investigated the risk factors and etiology of the canine oral mucosal melanoma (OMM) in dogs, 16S rRNA sequencing was used for microbiome analyses and found that the bacteria Tannerella forsythia and Porphyromonas gingivalis were found in significantly higher amounts in dogs with OMM and their presence could be considered a risk factor for the development of OMM in dogs [37]. Stashenko et al [35] colonized germ-free mice with different oral microbiomes and exposed them to a carcinogenic 4-nitroquinoline-1-oxide (4-NQO) agent.…”
Section: Introductionmentioning
confidence: 99%